Efficient Parking Management with Iot-Based Smart Parking System - Nikhath Sultana, Atiya, Syed Imroze Ahmed, Mohammed abdul bari (Mathematical Statistician and Engineering Applications, 2023)
This paper presents an automated smart car parking system that utilizes IR sensors to detect vehicles and provide feedback on available parking spaces in complex multi-storeyed parking structures. The system is designed to navigate drivers to the nearest available parking space using visual aids, effectively reducing search time. This cost-effective system is ideal for use in malls, IT hubs, and other parking facilities, and eliminates the need for expensive equipment and complex lines of code. The paper provides an overview of the system, including its functional and non-functional requirements, tools, and technologies used for prototype development and deployment. The system also includes a web-based application that allows users to reserve a parking space in advance. Field testing and demonstration results are discussed, highlighting the system's effectiveness in managing parking spaces and reducing labour requirements. The system's development and deployment offer valuable insights into creating a smart parking system that can enhance the overall user experience in a range of parking facilities. In summary, the automated smart car parking system presented in this paper provides an efficient and effective solution for managing parking spaces in multi-storeyed parking structures, thereby reducing search time and improving the overall user experience.